Can next-generation humanized mice that reconstituted with both functional human immune system and hepatocytes model the progression of viral hepatitis to hepatocarcinogenesis? - Guo, Jinglong; Wang, Siyue; Gao, Qi (Frontiers in Medicine, 2022)
Hepatitis B virus (HBV) and Hepatitis C virus (HCV) chronic infections cause liver immunopathological diseases such as hepatitis, fibrosis, cirrhosis, and hepatocellular carcinomas, which are difficult to treat and continue to be major health problems globally. Due to the species-specific hepato-tropism of HBV and HCV, conventional rodent models are limited in their utility for studying the infection and associated liver immunopathogenesis. Humanized mice reconstituted with both functional human immune system and hepatocytes (HIS-HuHEP mice) have been extremely instrumental for in vivo studies of HBV or HCV infection and human-specific aspects of the progression of liver immunopathogenesis. However, none of the current HIS-HuHEP mice can model the progression of viral hepatitis to hepatocarcinogenesis which may be a notorious result of HBV or HCV chronic infection in patients, suggesting that they were functionally compromised and that there is still significant space to improve and establish next-generation of HIS-HuHEP mice with more sophisticated functions. In this review, we first summarize the principal requirements to establish HIS-HuHEP mice. We then discuss the respective protocols for current HIS-HuHEP mice and their applications, as well as their advantages and disadvantages. We also raise perspectives for further improving and establishing next-generation HIS-HuHEP mice.